Preoperative Opioid Use is Associated with Inferior Patient Reported Outcomes and Prolonged Opioid Use after Patellofemoral Stabilization Surgery. Issue 7 (31st July 2020) - Khazi, Zain; Hajewski, Christina; Glass, Natalie; Wolf, Brian; Duchman, Kyle; Westermann, Robert; Bollier, Matthew; Shamrock, Alan
Objectives: The purpose of the study was to investigate the association between preoperative opioid use and persistent postoperative use, and determine the impact of preoperative opioid use on patient reported outcomes (PROs) in patients undergoing patellofemoral stabilization surgery. Methods: A retrospective analysis of 60 patients after patellofemoral stabilization surgery with a minimum of 2-year follow-up was performed using a prospectively-collected patellar instability registry. Patients were categorized as opioid naïve (n=48) or preoperative opioid users (n=12). Postoperative opioid use was assessed for all patients at 2 and 6 weeks. Knee Injury and Osteoarthritis Outcome Score (KOOS) and Kujala questionnaires were administered at baseline, and 6 months and 2 years postoperatively. Results: Preoperative opioid use was identified as an independent risk factor for postoperative opioid use at 2- and 6-weeks following surgery (p=0.0023 and p<0.0001, respectively). Preoperative opioid use was associated with significantly lower KOOS and Kujala scores at baseline, 6 months and 2 years postoperatively. Both groups significantly improved from baseline KOOS and Kujala scores at 6 months and 2 years postoperatively. Regardless of preoperative opioid use, opioid use at 6 weeks after surgery was associated with worse KOOS scores at 6 months and 2 years postoperatively. Conclusion: In patients undergoing patellofemoral stabilization surgery, preoperative opioid use was predictive of postoperative use. Additionally, preoperative opioid use was associated with worse PROs at 6 months and 2 years following surgery. Table 1. Comparison of KOOS Subscore between Opioid Naïve and Preoperative Opioid User Opioid Naïve (n=48) Preoperative Opioid Use (n=12) P-Value At Baseline KOOS ADL 75.0116.49 48.6519.80 0.0001* KOOS Pain 66.2117.52 39.1212.84 <0.0001* KOOS Symptom 59.6715.45 37.5016.79 0.0004* KOOS Quality of Life 32.1221.35 28.3024.04 0.6091 KOOS Sport 37.7326.09 20.0026.71 0.0105* At 6-Month Follow-up Visit KOOS ADL 90.5313.92 72.0623.79 0.0068* KOOS Pain 83.1517.01 66.6623.65 0.0339* KOOS Symptom 75.6218.15 71.4312.37 0.2492 KOOS Quality of Life 62.4522.00 51.4622.82 0.1095 KOOS Sport 67.2626.66 41.0031.69 0.0183* At 2-Year Follow up Visit KOOS ADL 94.5410.32 74.6023.06 <0.001* KOOS Pain 89.4314.41 68.1723.33 0.0004* KOOS Symptom 79.4617.32 66.9616.69 0.0249* KOOS Quality of Life 71.8821.57 40.1025.63 0.0003* KOOS Sport 77.5021.54 40.8325.66 <0.001* *significant finding (P<0.05); KOOS-Knee Injury and Osteoarthritis and Outcomes Score; ADL-Activities of Daily Living Table 2. Comparison of Kujala Scores between Opioid Naïve and Preoperative Opioid Users Time Point Opioid Naïve (n=32) Preoperative Opioid Use (n=9) P-Value At Baseline 41.8826.74 29.8920.08 0.1503 At 6-Month Follow up 78.6118.67 56.1023.01 0.0063* At 2 Year Follow up 83.4917.66 63.5820.63 0.0023* *significant findings (P<0.05)